Factors influencing the multinational banks’ decisions to curtail operations in russia: Does ESG matter? - Rohov, H.; Kolodiziev, O.; Yehorycheva, S.; Krupka, I.; Zaplatynskyi, M. (My University, 2024)
The paper is devoted to an under-researched topic of the international business community's reaction to Russia's armed aggression against Ukraine. It aims to evaluate how such factors as G7 and EU financial sanctions, institutional pressure, ESG ratings, and asset value of multinational banks in Russia influence their decisions to reduce activities in the invading country. The study was conducted based on the Yale CELI database of companies leaving and staying in Russia, using the classification tree method. The results of this study show that none of the banks headquartered in G7 and EU member states that had no or relatively little assets in Russia before the invasion are doing business there on a pre-war scale. Unlike banks headquartered in other countries, most of them either curtailed their presence in that market or exited. This indicates that financial sanctions imposed by G7 and EU member states and institutional pressure on banks in these countries to withdraw from the Russian market have proven effective to a certain extent. However, these factors do not meaningfully influence the business of multinational banks with significant assets in Russia. The study has not confirmed the hypothesis that a bank with higher ESG ratings is more likely to curtail its operations in the market of an aggressor country and withdraw. However, nearly all banks that scaled back significant activities or even pulled out of Russia have better ESG indicators than the industry average. The study results suggest the feasibility of improving the methodologies of ESG rating providers for accurately measuring business reactions to aggression and war crimes.
Keywords: banks; asset value; war and business; sanctions; market exit; ESG; SDG Impact rating